High-mannose glycans from Schistosoma mansoni eggs are important for priming of Th2 responses via Dectin-2 and prostaglandin E2 - Almeida, Luís; van Roey, Ruthger; Patente, Thiago Andrade; Otto, Frank; Veldhuizen, Tom; Ghorasaini, Mohan; van Diepen, Angela; Schramm, Gabriele; Liu, Jianyang; Idborg, Helena; Korotkova, Marina; Jakobsson, Per-Johan; et al. (Frontiers in Immunology, 2024)
The parasitic helminth Schistosoma mansoni is a potent inducer of type 2 immune responses by stimulating dendritic cells (DCs) to prime T helper 2 (Th2) responses. We previously found that S. mansoni soluble egg antigens (SEA) promote the synthesis of Prostaglandin E2 (PGE2) by DCs through ERK-dependent signaling via Dectin-1 and Dectin-2 that subsequently induces OX40L expression, licensing them for Th2 priming, yet the ligands present in SEA involved in driving this response and whether specific targeting of PGE2 synthesis by DCs could affect Th2 polarization are unknown. We here show that the ability of SEA to bind Dectin-2 and drive ERK phosphorylation, PGE2 synthesis, OX40L expression, and Th2 polarization is impaired upon cleavage of high-mannose glycans by Endoglycosidase H treatment. This identifies high-mannose glycans present on glycoproteins in SEA as important drivers of this signaling axis. Moreover, we find that OX40L expression and Th2 induction are abrogated when microsomal prostaglandin E synthase-1 (mPGES) is selectively inhibited, but not when a general COX-1/2 inhibitor is used. This shows that the de novo synthesis of PGE2 is vital for the Th2 priming function of SEA-stimulated DCs as well as points to the potential existence of other COX-dependent lipid mediators that antagonize PGE2-driven Th2 polarization. Lastly, specific PGE2 inhibition following immunization with S. mansoni eggs dampened the egg-specific Th cell response. In summary, our findings provide new insights in the molecular mechanisms underpinning Th2 induction by S. mansoni and identify druggable targets for potential control of helminth driven-Th2 responses.